Towards A More Socially Inclusive and Sustainable Framework for Islamic Banking and Finance - Ghani, Gairuzazmi M (International Journal of Economics, Management and Accounting, 2020)
Mainstream interest based financial system marginalized many Muslims as the system is in conflict with the principles of sharÄ«Ê¿ah (Islamic law). IslÄmic banking and finance (IBF) institutions aimed at promoting IslÄmic norms of economic behavior, and ultimately to realize the maqÄá¹£id al-sharÄ«â€˜ah have developed and offer sharÄ«Ê¿ah compliant financial instruments. The growth of IBF institutions has been phenomenal since their introduction in the 1960s. The upsurge of IBF in the 1970s was driven by oil price rises, competition for regional power between Egypt and Saudi Arabia, and a general IslÄmic resurgence. The second upsurge has involved similar drivers, but with the added benefit of standardized regulation and management, as well as improved overall business decision-making. The aftermath of 11 September 2001 reinforced the second surge in IslÄmic finance. However, IBF institutions have tended to respond to prevailing forces of the international financial system by moving closer to conventional financial institutional practice. IBF is supposed to expand the Muslim financial base and reduce financial exclusion, but many institutions have been taken over by pragmatic bankers who shift the core operation away from the original religious and social ideals. The new generation of financial instruments are at odds with the foundational axioms of IslÄmic economics. As such, the concept behind IBF has been reduced to the mere removal of ribÄâ€™ and the conduct of financial activities according to sharÄ«Ê¿ah derived contractual norms. IBF institutions are following the letter of the sharÄ«Ê¿ah, but not its spirit, the maqÄá¹£id. The simplistic â€˜pragmatismâ€™ may mean that the globalization and unprecedented growth of IBF would permeate the lives of many poorer disenfranchised Muslims. However, more recent developments in IBF such as iMFI and social impact á¹£ukÅ«k (IslÄmic bond) suggest that IBF is moving to a more socially inclusive and sustainable finance.